Synthesis and Characterization of Complexes of Cobalt(II), Nickel(II) and Copper(II) with Substituted Pyrazoline. - CHATIREE, N.S.; SHARMA , T.C. (Asian Journal of Chemistry, 2010)
Crystalline complexes of Co(II), Ni(II) and Cu(II) with ligand 3-phenyl 5-(2-hydroxyphenyl) pyrazoline have been synthesised by extraction method in a M : L ratio of 1 : 2. Finally extracted complexes are refluxed in benzene. The cobalt and copper complexes are paramagnetic whereas nickel is dimagnetic. The complexes of Co(II), Ni(II) and Cu(II) has been assigned as ML2 type showing Cu(II) of square-planer species and Co(II) and Ni(II) of six coordinated octahedral geometry.